Makna laba pada rumah makan gratis pendekatan studi fenomenologi - Mais, Rimi Gusliana; Nursanita, Nursanita; Wahyuni, Sinta Sri (Jurnal Manajemen, 2023)
This research aims to understand the views of the owners of the Ciangsana Free Restaurant in interpreting profits. This research is qualitative research using phenomenological methods. The phenomenological method is considered appropriate to use in this research because this research is unique and represents someone's life experience. Data collection methods in this research used interviews, observation, and literature study. This research shows that the owner of the Ciangsana Free Restaurant defines profit with 3K, namely tranquility, happiness, and blessings. The owner of the Ciangsana Free Restaurant interprets tranquility as a condition of living that is safe, peaceful, and without any relatives. The owner of Ciangsana Free Restaurant interprets profit happiness as a feeling of happiness because he can share it with others. Profit is interpreted as a blessing by the owner of the Ciangsana Free Restaurant as a form of blessing of good fortune that continues to flow endlessly, as the sufficiency of life given by Allah SWT. The blessings of life that are felt in the form of family health and the benefits of life towards others are an inspiration for goodness for many people.